Global Engagement in a Time of Geopolitical Tensions: A New Cold War - Altbach, Philip; de Wit, Hans (International Higher Education, 2022)
Global engagement has been a key priority of higher education and its internationalization, but is currently seriously challenged by geopolitical tensions. We seem to be returning to the political climate of the Cold War, which ended in the late 1980s. What lessons can we learn from academic cooperation during the first Cold War and during the academic boycott in South Africa, and how can we avoid returning to the isolated bubbles of engagement of that past?